Hubungan Kontrol Diri dan Konformitas Teman Sebaya dengan Perilaku Bullying di Madrasah Aliyah Alwasliyah 12 Perbaungan - Chairunnisa Safitri; Abdul Munir; Hasanuddin Hasanuddin (Mahesa Research Center, 2022)
This study aims to determine the relationship between self-control and peer conformity with bullying behavior at Madrasah Aliyah Al-Wasliyah 12 Perbaungan. This type of research is quantitative research with correlational method. The measuring instrument used is the Likert scale to measure self-control and peer conformity with bullying behavior. The data analysis method used in this research is multiple regression analysis. The population in this study were 435 people with a sample of 140 people by screening students who behaved in bullying and the test results became 110 people. The sampling technique is total sampling. The subjects in this study were students at MA Alwasliyah 12 Perbaungan with the results of the study showing that: (1) There was a significant negative relationship between self-control and bullying behavior (2) there is a significant negative relationship between peer conformity and behavior bullying of students at MA Al-Wasliyah 12 Perbaungan (3) There is a significant relationship between self-control and peer conformity with bullying behavior From this result, it is known that there are still 69.7% contributions from other factors or variables to the formation of bullying behavior. From the results of this research, the proposed hypothesis is accepted.